One nation [compact disc, unabridged] : what we can all do to save America's future - Carson, Ben (Penguin Audio, 2014)
Dr. and Mrs. Carson offer a bold plan to stop the country's slide into fiscal and moral decay. Avoiding the political correctness of politicians and the animosity of Washington lawyers, Dr. Carson calls for respectful discussion and disagreement, with no subjects off limits. Applying the problem-solving skills he honed as a surgeon, he takes on tough issues such as education, health care, family values, race relations, taxes, charity, and the role of faith in public life.